Morphometry of The Reproductive Organs of Female Bandicoots (Echymipera kalubu) - Rafli, Fahry; Tethool, Angel Novita; Pattiselanno, Freddy (Jurnal Veteriner, 2021)
Information about bandicoots in Papua is very limited, because most of the studies conducted are focusing on ecology with study areas in other parts of Indonesia New Guinea. Our knowledge about the reproductive organs of bandicoots, especially females as a local genetic source, is almost completely non-existent. Meanwhile, on the other hand, the development of captive breeding efforts for endemic Papuan animals including bandicoots is currently a concern. Therefore, research on the reproductive organs of female bandicoots is very urgent to get an idea of   the reproductive organs that play an important role in the development of captive breeding program. This research was conducted at the Laboratory of Physiology and Animal Reproduction, Faculty of Animal Husbandry, University of Papua from 15 June to 15 September 2017. The reproductive organs of female bandicoots were obtained from female bandicoots hunted around Manokwari. Three female reproductive organs of the bandicoot (Echymipera kalubu) were used in this study, and the morphology of their reproductive organs was observed according to the purpose of the study. As a comparison the reproductive organs of D. minustus were used in this study. The results showed that the female reproductive organs of E. kalubu had an “advanced duplex” type with a pair of ovaries, fallopian tubes, uterus, vaginal cul de sac, cervix and lateral vagina. Morphologically, the reproductive organs of E. kalubu have a certain uniqueness, different from the reproductive organs of other female marsupials, so they need serious attention in developing captive breeding program in the near future.